2020
DOI: 10.1186/s12906-019-2787-y
|View full text |Cite
|
Sign up to set email alerts
|

Study on the mechanisms of compound Kushen injection for the treatment of gastric cancer based on network pharmacology

Abstract: Background: As an effective prescription for gastric cancer (GC), Compound Kushen Injection (CKI) has been widely used even though few molecular mechanism analyses have been carried out. Methods: In this study, we identified 16 active ingredients and 60 GC target proteins. Then, we established a compound-predicted target network and a GC target protein-protein interaction (PPI) network by Cytoscape 3.5.1 and systematically analyzed the potential targets of CKI for the treatment of GC. Finally, molecular dockin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 60 publications
1
15
0
Order By: Relevance
“…In recent years, the application of network pharmacology, RNA-Seq technology, and bioinformatics has become a good research tool for screening bioactive ingredients with anti-cancer properties and predicting target genes and related signaling pathways. The application of in vitro cells and in vivo animal models has also provided robust technical support for verifying the biological effects of CKI [16][17][18][19][20][21][22][23][24][25][26][27] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, the application of network pharmacology, RNA-Seq technology, and bioinformatics has become a good research tool for screening bioactive ingredients with anti-cancer properties and predicting target genes and related signaling pathways. The application of in vitro cells and in vivo animal models has also provided robust technical support for verifying the biological effects of CKI [16][17][18][19][20][21][22][23][24][25][26][27] .…”
Section: Discussionmentioning
confidence: 99%
“…A TCM network pharmacology approach provides a new research paradigm for translating TCM from experience-based medicine to evidence-based medicine, which will likely accelerate TCM discovery and improve drug discovery strategies 15 . A combination of network pharmacology and experimental verification has gradually become an important way to study the mechanism of action of CKI [16][17][18] .…”
Section: Introductionmentioning
confidence: 99%
“…Research showed that 20-200 µg/mL Radix Sophorae Flavescentis could induce apoptosis of human gastric cancer cells by downregulating Bcl-2 and upregulating Bax [29]. In addition, a network pharmacology method predicted that CKI inhibited the growth and metastasis of gastric cancer cells by regulating vital targets and important related pathways [30]. Previous research confirmed that five compounds (sophocarpine, matrine, oxymatrine, oxysophocarpine, and xanthohumol) of Radix Sophorae Flavescentis exerted anti-prostate cancer effects by affecting cell proliferation and apoptosis [31].…”
Section: Discussionmentioning
confidence: 99%
“…At present, the identification methods of chemical compositions of traditional Chinese medicine (TCM) mainly include thin-layer chromatography (TLC), capillary electrophoresis (CE), highperformance liquid chromatography (HPLC), gas chromatography (GC), ultraviolet (UV) spectrophotometry, etc. [19][20][21][22] However, there are many types of chemical ingredients in TCM and the content of some active ingredients is extremely low. Therefore, it is difficult to make accurate qualitative or quantitative analysis of TCM ingredients using traditional analytical methods.…”
Section: Introductionmentioning
confidence: 99%